Polymers in diffusion artistic styles epoch - García Díez, Sergio (Arte, Individuo y Sociedad, 2009)
This work raises the arrival of the synthetic resins to the artistic fact after 2 ª World War. We will be able to know which are the specific characteristics of some polymers for which some artist have felt attracted and have decided to make them his (yours) to adapt them to what they want to express in his volumetric creations or what aesthetic purpose they search with his employment. In general, the sculptors have used the plastic ones whose properties more are adapted to the narrative plastic speech for that they look to execute his works, and that had not been possible with other materials.